Benefit Sharing at Scale : Good Practices for Results-Based Land Use Programs - World Bank Group (World Bank, Washington, DC, 2019)
Land use initiatives that distribute result-based payments for emission reductions need to define transparent and equitable benefit-sharing plans for how these incentives flow to a diverse range of stakeholders. This study synthesizes good practices for benefit sharing in jurisdictional land use programs that make results-based payments for emission reductions. The report draws lessons from large-scale programs and other relevant initiatives that involve benefit sharing focused on forests, land use, natural resources, and climate change. The analysis is designed to support government and program staff in developing and implementing benefit-sharing arrangements for jurisdictional level results-based land use programs, including participant countries of the World Bank’s Forest Carbon Partnership Facility (FCPF) and BioCarbon Fund Initiative for Sustainable Forest Landscapes (ISFL).